Urban Community Schools: Educator Perceptions of the Effects of Children's Health and Wellness on Learning - Diana J. LaRocco; Beth A. Taylor; Suzanne Cordier D'Annolfo (Arizona State University, 2014)
Findings from a participatory action-research project that brought together 11 individuals from five of Hartfords seven community schools to engage in a focus group discussion about the effects of childrens health and wellness on learning are presented. The researchers and key personnel from Hartford Public Schools and Achieve Hartford! co-constructed the inquiry. Issues identified as interfering with student learning clustered into themes that include students and family members mental, behavioral, nutritional, and domestic/neighborhood health. The results are being used to create a call for translational research proposals for University researchers to address these questions and disseminate findings to Hartford Public Schools and related community partners.